Comparison of the Effectiveness of Bath and Massage in Bilirubin Levels in Neonates - Khadijeh Dehghani; Effat Nouroozi; Zahra Mandegari; Naiire Salmani; Mehrdad Shakiba (Mashhad University of Medical Sciences, 2019)
Background: Jaundice is one of the most common health problems among neonates, involving almost 60% of full-term newborns, therefore requiring consequent phototherapy. Since phototherapy has several complications, considering alternative treatments has long been of pivotal importance. Therefore, the present study aimed at comparing the effectiveness of bath and massage in bilirubin levels in neonates. Methods: This was a randomized clinical trial conducted on neonates who were born in Zeyaei Hospital in Ardakan, Iran, in 2018. A total of 90 neonates were selected using the convenience sampling method and then assigned into two intervention groups (i.e., bath group and massage group) and a control group through random allocation method. In the bath group, the neonates were bathed immediately after birth. In the massage group, the neonates received field massage twice a day each lasting 15 min for 5 consecutive days. The neonates belonging to the control group were served with routine care. The jaundice meter China 800 (jk) device was used to measure the skin bilirubin levels of the neonates in the three groups in a scheduled manner (i.e., days 1, 3, 5, and 7) at 9 a.m. The data were analyzed using the ANOVA, Chi-square test, Tukey's post hoc test, and repeated measures ANOVA in SPSS software (version 18). Results: There was no significant difference between the mean bilirubin scores of the three groups over the first, third, and fifth days. A significant difference was found between the mean bilirubin scores of the bath and massage groups compared with that of the control group on the seventh day (P=0.001). Also, no significant difference was seen between the mean bilirubin levels of the bath and massage groups on the seventh day. Conclusion: The findings revealed that there was no difference between the bath and massage techniques in reducing neonatal jaundice. Therefore, both techniques can be utilized in this regard.